Integral of (2x-3) dx
The solution
Detail solution
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2xdx=2∫xdx
-
The integral of xn is n+1xn+1 when n=−1:
∫xdx=2x2
So, the result is: x2
-
The integral of a constant is the constant times the variable of integration:
∫((−1)3)dx=−3x
The result is: x2−3x
-
Now simplify:
x(x−3)
-
Add the constant of integration:
x(x−3)+constant
The answer is:
x(x−3)+constant
The answer (Indefinite)
[src]
/
| 2
| (2*x - 3) dx = C + x - 3*x
|
/
The graph
Use the examples entering the upper and lower limits of integration.